Does shift-and-persist strategy buffer career choice anxiety and affect career exploration? - Sumin Lee; Ryota Kobayashi; Mami Oda; Yoshihide Noritake; Ken’ichiro Nakashima (BMC Research Notes, 2022)
Abstract Objective The transition from school to the workforce is important for concrete future planning. During this period, people are more likely to experience psychological health problems, such as anxiety and feelings of hopelessness and helplessness. In particular, job hunting in individuals with low socioeconomic status (SES) leads to various impulsive behaviors and physical and psychological problems due to a scarcity of economic and time resources. There is a lack of research examining career education and intervention approaches that consider the backgrounds of those experiencing adversities and difficulties due to low SES. Considering these situations, we examined whether shift-and-persist coping strategies (S-P) could buffer the career choice anxiety of individuals with low SES and improve career exploration. Results The results from 311 students who preparing/doing for job hunting showed a negative association between S-P and career choice anxiety and a positive association with career exploration. There are no significant effects of the direct link between SES to career exploration and the indirect link between SES and career exploration via career choice anxiety. There was also no buffering effect of S-P use on the above mediating process.